1996
DOI: 10.1002/qsar.19960150405
|View full text |Cite
|
Sign up to set email alerts
|

Quantum‐chemical Descriptors for Estimating the Acute Toxicity of Electrophiles to the Fathed minnow (Pimephales promelas): An Analysis Based on Molecular Mechanisms

Abstract: Estimating the toxicity of reactive xenobiotics to aquatic organisms requires physicochemical descriptors of passive transport and chemical reactions with nucleophilic biological ligands. Herein, electrophiles whose toxic action is attributed to nucleophilic substitution (SN), Michael-type addition and Schiff-base formation were examined. Training sets for each molecular mechanism were generated through substructure search applied to chemicals in a fathead minnow (Pimephules promelus) database. Based on a deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 31 publications
5
89
0
2
Order By: Relevance
“…Taking into consideration the results of the present study and those of published literature 6,23) , it could be claimed that acrylates with a high GSH reactivity showed higher toxicity than methacrylates with a low GSH reactivity.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Taking into consideration the results of the present study and those of published literature 6,23) , it could be claimed that acrylates with a high GSH reactivity showed higher toxicity than methacrylates with a low GSH reactivity.…”
Section: Discussionsupporting
confidence: 61%
“…In previous studies 6,23) , acrylates such as EAA and iBAA were reported to exhibit markedly greater toxicity than methacrylates such as MMA and iPMA in fathead minnow or mice. Taking into consideration the results of the present study and those of published literature 6,23) , it could be claimed that acrylates with a high GSH reactivity showed higher toxicity than methacrylates with a low GSH reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach has also been successful to estimate toxicity in aquatic organisms (Karabunarliev et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…On the comparative introduce, a causal connection between Invivo LD 50 in mice and or log k esteem for 2-hydroxyethyl acrylate (2HEA) and ethyl acrylate (EA). This was proven by looking at the individual information for 2HEA (log P=-0.21, esteem=3.214 eV, separately) to EA (log P=1.33, esteem=3.1981 eV, individually); i.e., both have for all intents and purposes comparable values, yet altogether unique response rates (log k=1.92 versus 1.43, individually) and dangerous potencies (LD 50 =5.2 m mol/kg versus 18 m mol/kg, separately) [23]. Take note of that the δ C β estimation of 2HEA is 130.4 ppm, though EA is 130.24 ppm.…”
Section: Periodontics and Prosthodonticsmentioning
confidence: 99%
“…Dynamic acrylates, for example, 2HEA, MA, EA and iBA were already answered to demonstrate notably more prominent poisonous quality in fathead minnow or mice than methacrylates, for example, MMA [6,17]. Acrylates with a high GSH reactivity indicate higher lethality than methacrylates with a low GSH reactivity [6,23]. Then again, in spite of the fact that allylMA indicates bring down GSH reactivity than the acrylates EA and iBA, AllyMA demonstrated more noteworthy lethality than the last [22].…”
Section: Toxic Intermediates Of Monomers In Different Metabolic Transmentioning
confidence: 99%